Epithelioid hemangioendothelioma lung - Finozzi, Vivian; Andrade, Eduardo; Campos, Néstor; Pizarrosa, Carlos (Cirugía del Uruguay, 2000)
The first national case of epithe/ioid lung hremangioendiothe/ioma concerned a 60-year-old woman. Clinical picture and TC diagnosis showed a vascularized tumor producing persistent hremoptoic expectoration. lt is necessary to be acquainted with it far the purpose of a differentiated diagnosis. lt is a tumor with specific immunohistochemical markers against factor VIII